The Influence of Competence and Workload on the Quality of Financial Report Preparation at the Naval Technology College - Budiawan, Isma; Pakpahan , Faurna Lusiani; Harahap , Iman Rahmadsyah (Journal of Industrial Engineering & Management Research, 2025)
The purpose of this study is to analyze the effect of competence and workload on the quality of financial statement preparation at STTAL (Sekolah Tinggi Teknologi Angkatan Laut) using 100 respondents as sampel who are directly involved in financial statement preparation. Analyzing of the datas were using multiple linear regression with the support of SmartPLS software. The results show that competence has a positive and significant effect on the quality of financial statements (p-value = 0.038). Similarly, workload also has a positive and significant effect (p-value = 0.000). Simultaneously, competence and workload significantly affect the quality of financial statements with an F-value of 13.898 (p-value = 0.000). The R² value of 0.223 indicates that the independent variables explain 22.3% of the variation in financial statement quality. This study contributes empirically by demonstrating that managing employee competence and balancing workload are critical factors in improving the quality of financial statements in military higher education institutions. Theoretically, this research enriches the literature on human resource management and public sector accountin.